Efektivitas Program Penyuluhan Pertanian dalam Peningkatan Pengetahuan Petani tentang Bercocok Tanam Padi Organik di Desa Waode Buri Kecamatan Kulisusu Utara Kabupaten Buton Utara - Nastin, Nastin; Sidu, Dasmin; Mappasomba, Musadar (Jurnal Ilmiah Membangun Desa dan Pertanian, 2019)
This study aims to find out what extension programs implemented by extension agents in the development of organic rice, the level of knowledge of farmers in organic rice farming activities, and the effectiveness of agricultural extension programs conducted in WaodeBuri Village can be said to be effective or ineffective. The data analysis method used descriptive data analysis, Likert Scale analysis using the interval formula class I = J / K and using the formula for the effectiveness. Population and sample were obtained in the census, namely 1 organic rice farmer group consisting of 10 people and an agricultural instructor. Collecting data using research in the field and interviews. The results of this study indicate that extension programs in the development of organic rice have not been realized by extension, the level of knowledge of farmers in organic rice farming activities is in a low category, and the effectiveness of agricultural extension programs conducted in WaodeBuri Village is declared to be quite effective at 62%.